Fish consumption, purchasing behaviour and perception of Fish quality with especial reference to sardine - OLEYA EL HARIRI; NOURREDINE BOUCHRITI; LAHOUSSAINE BAAMAL; RACHID BENGUEDDOUR (International Journal of Pharma and Bio Sciences, 2018)
The objective of this study is to assess the level and frequency of purchase and consumption of fish in the World and especially in Morocco. Moreover, it is aimed to explore preference of fish consumers, and to investigate the level of perception of quality and histamine poisoning experiences. A consumption survey was conducted by interviewing 802 individuals using a questionnaire. The study found that the level of consumption and purchase of various fish species is variable and the most consumed fish is sardine. The per capita fish consumption is almost 17 kg per year with nearly 64 percent as fresh sardine (10.4 Kg). This level is only 85 percent of the figure advanced by FAO in 2016. Grilling is by far the favored method of preparation of sardine (49.5%). The level of perception of food quality is good. Indeed, the majority approves the importance of the cold chain and good hygienic practices for fish preservation, but some practices reported still could promote the risk of histamine poisoning. The Moroccans fish consumption profile lacks diversity and does not reflect the diverse natural resources in Morocco. Hence, Moroccans need to extend their fish consumption to other species.